PERILAKU KEAMANAN PANGAN DENGAN KUALITAS IKAN ASAP DI PASAR KOTA TERNATE - Fahmi Abdul Hamid (Jurnal Riset Kesehatan, 2018)
Fish is one of food comodity which is perishable, because of it high nutrient content such as protein (18-30%) and water (70-80%), as are their effects as a good media to multiply the rotten bactery. The aim of this study is to recognize the association of food safety behaviour with the Cakalang Smoked Fish in Ternate’s market. This is a quantitative study with the correlational approach. The research was conducted in Ternate’s city on November until December 2017. Total sample of this study are 30 samples with Simple Random Sampling method. Food safety behaviour was evaluated using the reliable and valid checklist while smoked fish quality was evaluated using the SNI 01-2332.1-2006 method.This study showed that the average of food sanitation behaviour was 2,7083 with the deviation standart ±3,55200. Based on microbiologically asessment, data showed that 25 samples was categorized negatively or was not contamined by Escherichia Coli  bactery and 5 samples was categorized positively or was contamined by Escherichia Coli  bactery. The average score of contamination is 4,5333 APM/g with the deviation standart ±2,28619 APM/g. The correlation method of statistic result showed a positive correlation between food safety behaviour and the smoked fish quality at p 0,01 less than α 0,05  and the correlation score is 0,507**. This study conclude a correlation between food safety behaviour and the smoked fish quality. It suggest to make a food safety training and to continue the research about the hygiene of equipment that was used by the cakalang smoked fish seller microbiologically.Key word : Behaviour, Food Safety, Smoked Fish Quality